The Impact of Hexane on the Dynamic Viscosity of Kazakhstans’s Heavy Oil - Logvinenko, Alexandr (Engineering, Technology & Applied Science Research, 2025)
The Republic of Kazakhstan has significant amount of heavy oil and natural bitumen reserves. Some of that reserves have high viscous oil more than 1000 mPa*s at shallow depth. The main recovery technique is thermal methods using steam or hot water injection. One of the variants to improve thermal methods is to add liquid or gaseous solvent. In our research we consider hexane as an additive solvent. The purpose of this study is to determine how hexane affects to dead heavy oil of Sarybulak field within the context of dynamic viscosity reduction. Mix of heavy oil and hexane in various proportions are obtained. Also, dependences of heavy oil dynamic viscosity on the hexane content are considered.